Access to innovative medicines for metastatic melanoma worldwide: Melanoma World Society and European Association of Dermato-oncology survey in 34 countries. (November 2018) - Kandolf Sekulovic, L.; Guo, J.; Agarwala, S.; Hauschild, A.; McArthur, G.; Cinat, G.; Wainstein, A.; Caglevic, C.; Lorigan, P.; Gogas, H.; Alvarez, M.; Duncombe, R.; et al.
Abstract: According to data from recent studies from Europe, a large percentage of patients have restricted access to innovative medicines for metastatic melanoma. Melanoma World Society and European Association of Dermato-oncology conducted a Web-based survey on access to first-line recommended treatments for metastatic melanoma by current guidelines (National Comprehensive Center Network, European Society for Medical Oncology [ESMO] and European Organization for Research and Treatment of Cancer/European Association of Dermato-oncology/European dermatology Forum) among melanoma experts from 27 European countries, USA, China, Australia, Argentina, Brazil, Chile and Mexico from September 1st, 2017 to July 1st, 2018. Data on licencing and reimbursement of medicines and the number of patient treated were correlated with the data on health expenditure per capita (HEPC), Mackenbach score of health policy performance, health technology assessment (HTA), ASCO and ESMO Magnitude of clinical benefit scale (ESMO MCBS) scores of clinical benefit and market price of medicines. Regression analysis for evaluation of correlation between the parameters was carried out using SPSS software. The estimated number of patients without access in surveyed countries was 13768. The recommended BRAFi + MEKi combination and anti-PD1 immunotherapy were fully reimbursed/covered in 19 of 34 (55.8%) and 17 of 34 (50%) countries, and combination anti-CTLA4+anti-PD1 in was fully covered in 6 of 34 (17.6%) countries. Median delay in reimbursement was 991 days, and it was in significant correlation with ESMO MCBS (p = 0.02), median market price (p = 0.001), HEPC and Mackenbach scores (p < 0.01). Price negotiations or managed entry agreements (MEAs) with national authorities were necessary for reimbursement. In conclusion, great discrepancy exists in metastatic melanoma treatment globally. Access to innovative medicines is in correlation with economic parameters as well as with healthcare system performance parameters. Patient-oriented drug development, market access and reimbursement pathways must be urgently found. Highlights: New therapies have dramatically improved the prognosis of metastatic melanoma, but disparities in access to these medicines exist worldwide. BRAFi+MEKi combinations are fully reimbursed in 17 of 34 (50%) countries. Anti-PD1 immunotherapies are fully reimbursed in 17 of 34 (50%) countries. Combination immunotherapy (anti-CTLA4+anti-PD1) is reimbursed in 9 of 34 (26.4%) countries, in 3 countries with restrictions. Patient-oriented research, development, market access and reimbursement mechanisms must be urgently developed.